Bio-tribocorrosion in dental applications - Rocha, L. A. [UNESP]; Oliveira, F.; Cruz, H. V.; Sukotjo, C.; Mathew, M. T. (Elsevier, 2013)
In the oral cavity, materials (including our natural teeth) are exposed to a complex environment, which results in simultaneous mechanical, electrochemical, and microbiological solicitations. Therefore, bio-tribocorrosion is an important cause of degradation of dental materials leading to functional and/or biological detrimental effects due to an increased release of metallic ions and wear debris. This chapter describes the main bio-tribocorrosion phenomena that occur in the oral environment, and discuss the main parameters related to both the materials and the environment affecting bio-tribocorrosion in dental applications. © 2013 Woodhead Publishing Limited All rights reserved.
Keywords: Bio-tribocorrosion; Corrosion; Dentistry; Wear